Analysis of Additional Teaching Materials for 8th Grade Junior High School - Sari, Sinta Kumala; Dimas, Arifian (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
This study aims to examine the need for additional teaching materials for science learning among students at MTs Negeri 2 Ngawi. This study uses a research and development method known as Research and Development (RnD). This research development model was adapted from the development of 4D-Models (define, design, development, and dissemination). The subjects in this study were class VIII students of MTs Negeri 2 Ngawi. Observations on science learning, interviews with teachers and students, and the distribution of questionnaires on the need for additional teaching materials indicate that in addition to the textbooks already owned by students, additional teaching materials are also needed according to the characteristics of students. The textbooks owned by students also have several shortcomings, ranging from the limited material presented and the lack of experimental exercises. This research was conducted to explore the analysis of student needs and classroom conditions to find solutions for the development of teaching materials to be used. The results of this study can be concluded that students need teaching materials that allow them to conduct direct experiments to receive the material effectively.